5′ to 3′ mRNA Decay Factors Colocalize with Ty1 Gag and Human APOBEC3G and Promote Ty1 Retrotransposition - Dutko, James A. (American Society for Microbiology (ASM), 2010)
The genomic RNA of retroviruses and retrovirus-like transposons must be sequestered from the cellular translational machinery so that it can be packaged into viral particles. Eukaryotic mRNA processing bodies (P bodies) play a central role in segregating cellular mRNAs from the translational machinery for storage or decay. In this work, we provide evidence that the RNA of the Saccharomyces cerevisiae Ty1 retrotransposon is packaged into virus-like particles (VLPs) in P bodies. Ty1 RNA is translationally repressed, and Ty1 Gag, the capsid and RNA binding protein, accumulates in discrete cytoplasmic foci, a subset of which localize to P bodies. Human APOBEC3G, a potent Ty1 restriction factor that is packaged into Ty1 VLPs via an interaction with Gag, also localizes to P bodies. The association of APOBEC3G with P bodies does not require Ty1 element expression, suggesting that P-body localization of APOBEC3G and Ty1 Gag precedes VLP assembly. Additionally, we report that two P-body-associated 5′ to 3′ mRNA decay pathways, deadenylation-dependent mRNA decay (DDD) and nonsense-mediated decay (NMD), stimulate Ty1 retrotransposition. The additive contributions of DDD and NMD explain the strong requirement for general 5′ to 3′ mRNA degradation factors Dcp1, Dcp2, and Xrn1 in Ty1 retromobility. 5′ to 3′ decay factors act at a posttranslational step in retrotransposition, and Ty1 RNA packaging into VLPs is abolished in the absence of the 5′ to 3′ exonuclease Xrn1. Together, the results suggest that VLPs assemble in P bodies and that 5′ to 3′ mRNA decay is essential for the packaging of Ty1 RNA in VLPs.